2014
DOI: 10.1136/heartjnl-2013-304845
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cyclosporin-A on peri-operative myocardial injury in adult patients undergoing coronary artery bypass graft surgery: a randomised controlled clinical trial

Abstract: ObjectiveCyclosporin-A (CsA) has been reported to reduce myocardial infarct size in both the experimental and clinical settings. This protective effect is dependent on its ability to prevent the opening of the mitochondrial permeability transition pore, a critical determinant of cell death in the setting of acute ischaemia-reperfusion injury. Whether CsA can reduce the extent of peri-operative myocardial injury (PMI) in patients undergoing coronary artery bypass graft (CABG) surgery is unknown, and is investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 17 publications
(21 reference statements)
2
51
0
Order By: Relevance
“…303,317 Cyclosporine A is a drug which inhibits cyclophilin D, can thus inhibit MPTP opening, and ultimately also reduce IS in experimental studies, [318][319][320][321][322] but also in humans with reperfused AMI 323 and elective coronary artery bypass grafting. 324 The MPTP not only plays a central role in mitochondrial and cellular death or survival, but is also a point of convergence of cardioprotective signaling. In particular, inhibition of GSK 3β was proposed to integrate all upstream signals and exert an inhibitory effect on MPTP opening.…”
Section: Mitochondrial Permeability Transition Porementioning
confidence: 99%
“…303,317 Cyclosporine A is a drug which inhibits cyclophilin D, can thus inhibit MPTP opening, and ultimately also reduce IS in experimental studies, [318][319][320][321][322] but also in humans with reperfused AMI 323 and elective coronary artery bypass grafting. 324 The MPTP not only plays a central role in mitochondrial and cellular death or survival, but is also a point of convergence of cardioprotective signaling. In particular, inhibition of GSK 3β was proposed to integrate all upstream signals and exert an inhibitory effect on MPTP opening.…”
Section: Mitochondrial Permeability Transition Porementioning
confidence: 99%
“…ageing population and the prevalence of comorbidities such as diabetes, heart failure, previous myocardial infarction and renal impairment, much higher risk patients are undergoing the CABG surgery (8)(9)(10) consequently an enhanced degree of oxidative stress. Therefore, novel therapeutic approaches are needed to provide further cardiac protection.…”
Section: Introductionmentioning
confidence: 99%
“…The CicloMulsion preparation has been found to have similar pharmacokinetics and rather fewer adverse effects compared to Sandimmune preparation [25]. A study done on patients undergoing coronary artery bypass grafting surgery found no significant difference between the peak troponin T in CsA and placebo groups, except for the high-risk group with prolonged surgery -it showed that the extent of perioperative myocardial infarction was reduced in high-risk CsA patients [26]. Another RCT done in patients undergoing surgery for aortic stenosis showed a significant difference in the area under the curves for troponin I that favored the CsA group [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors did not report adverse events and mortality data. It included three of the RCTs included in our analysis, along with one RCT in patient undergoing coronary artery bypass surgery and one RCT in patient undergoing surgery for aortic stenosis [19,23,24,26,27]. Additionally, two of the larger trials comparing the effect of cyclosporine in acute myocardial infarction have been published recently and were not included in this study.…”
Section: Discussionmentioning
confidence: 99%